Determinants of Customers' Continuance Intention to Use Chatbots in e-Commerce - Quang, Huy Tran (Archives of Business Research, 2024)
Artificial intelligence (AI) has revolutionized the e-commerce experience and opened up new ways for businesses to communicate with customers through chatbots. This study aims to investigate how factors of chatbots influence continuance intention in e-commerce. A quantitative approach was adopted to explore the impact of interactivity, compatibility, information quality, service quality on perceived usefulness, perceived enjoyment of chatbots. It also aims to explore the determinants of continuance intention in chatbot use. Empirical data is collected from 476 participants through an online survey using Google Form and analyzed using regression analysis by IBM SPSS software. The results of the study show that compatibility, information quality, service quality positively affect perceived usefulness and perceived enjoyment of chatbot. Perceived usefulness and perceived enjoyment are found to have significant influence on continuance intention. The study contributes to the literature of consumer behavior regarding technology adoption. It also contributes to the refinement of the TAM and presents practical insights to managers, chatbot designers, and customer service units in improving chatbots and enhancing continuance intention.